INVESTIGATING THE ARCHITECT OF GRAND MOSQUE OF AL-MASHUN MEDAN, NORTH SUMATRA, INDONESIA – PART 1 - Budi, Bambang Setia; Kemalasari, Jeumpa (Journal of Islamic Architecture, 2018)
This study aimed to investigate the architect of the Grand Mosque of Al-Mashun Medan, North Sumatra, Indonesia. Four persons are alleged to be the architect of the mosque, which was built by the Sultan of Deli, Makmun Al-Rasyid Perkasa Alamsyah from 1906-1909. Their names are Adolf J. Dingemans, J.A. Tiendemans, Klingenberg, and Theo van Erp. All of them are Dutch. However, who was the real architect of the mosque remains uncertain. The four names are mentioned in many sources, but no evidence or argumentation is provided. The attributions will be critically examined to find out who is the most likely candidate. The method of this research was a critical review and descriptive analysis of all the collected information, and the interpretation of some physical evidence from the field survey. However, this research did not find who indeed the architect of the Grand Mosque of Al-Mashun Medan. The attribution still needs to carefully investigated because the more definite evidence is still required. It only found that the most convincing assumption is that the architect of the mosque is Theo van Erp.